PD-L1 expression in invasive solid papillary breast carcinomas - Sevdegul Aydın Mungan; Zeynep Sagnak Yılmaz; Ismail Saygın; Emel Cakır; Safak Ersoz; Umit Cobanoglu (Wolters Kluwer Medknow Publications, 2022)
Background: Invasive solid papillary carcinomas (ISPC) are rare malignant neoplasms in the classification of WHO 2019 breast tumors. Aims: We aimed to investigate the correlations between programmed cell death ligand-1 (PD-L1) expression status of tumor and immune cells and clinicopathological parameters by molecular classification of this rare morphological subtype. This study will contribute to the literature about the PD-L1 expression state of ISPCs for the first time. Material and Methods: The study included 19 invasive solid papillary carcinoma cases diagnosed between 2009 and 2019 in Pathology Department. Molecular subtyping was performed in 19 cases by immunohistochemical studies (ER/PR, Her-2/neu, Ki-67), and PD-L1 expression was evaluated in neoplastic and immune cells. Results: PD-L1 expression was detected in 4 (21%) cases, 3 (75%) of them were in luminal B and 1 (25%) were in the luminal A group. The correlation between molecular subtypes and PD-L1 expression was statistically significant (P = 0.016). Patients with PD-L1 expression had a higher Ki-67 index than patients without PD-L1 expression (P = 0.037). In addition, there was a statistically significant correlation between PD-L1 expressions of intratumoral lymphocytes and PD-L1 expressions of neoplastic cells (P = 0.004). Conclusions: While predicting the group that will benefit more from immunotherapy in solid papillary carcinoma cases, not only PD-L1 expression of tumor cells but also PD-L1 expression in tumor infiltrating lymphocyte (TIL) can help. In addition, PD-L1 staining rates of tumor cells as well as clinicopathological parameters (molecular subtype, high Ki-67 index, presence of TIL) can be predictive about immunotherapy.